Enhanced charge transfer with Ag grids at electrolyte/electrode interfaces in solid oxide fuel cells. Issue 12 (19th January 2016) - Choi, Mingi; Hwang, Sangyeon; Byun, Doyoung; Lee, Wonyoung
Abstract : This paper demonstrated the effect of Ag grids at the electrolyte/electrode interfaces on the electrochemical performance of solid oxide fuel cells (SOFCs). Abstract : We systematically investigated the effect of Ag grids at the electrolyte/electrode interfaces on the electrochemical performance of solid oxide fuel cells (SOFCs). Electrohydrodynamic jet printing was employed to fabricate Ag grids with a precise control of the geometry. A substantial reduction in the polarization resistance was observed when the pitch of the Ag grids decreased from 400 to 50 μm, indicating enhanced charge transfer through efficient supply and distribution of electrons along the Ag grids at the electrolyte/electrode interfaces. Our results demonstrate the possibility of engineering interfaces with metallic grids to achieve enhanced electrochemical performances for SOFCs operating at intermediate temperatures.